Improving students’ motivation and collaborative skills through Remap Jigsaw learning combined with modelling activities - Indriwati, Sri Endah; Susilo, Herawati; Hermawan, I Made Surya (University of Muhammadiyah Malang, 2019)
Students’ motivation and their collaborative skills play a crucial role in determining the learning quality. The lower the motivation and collaborative skills the lower the learning quality. This lesson study-based classroom action research aimed at improving the students’ learning motivation and collaborative skills by implementing a Remap Jigsaw learning model. The subjects of this research were the fifth semester undergraduate students of Biology Education of Universitas Negeri Malang, who were taking the Basic Skills of Teaching course. The research was conducted in four cycles in which the each cycle consisted of two meetings. The instruments of data collection were the observation sheets and assessment sheets of students’ self-report. The data was analyzed qualitatively and quantitatively. The results showed that students’ learning motivation increased from 66.25% in the cycle I to 84.37% in the cycle IV; while the students’ collaborative skills enhanced from 50% to 70.83% in the cycle IV. In the other words, the Remap Jigsaw combined with modelling activities can improve students’ motivation and their collaborative skills.